Unilex. Słownik uniwersytecki niemiecko-polski - Błażek, Agnieszka; Schaeder, Burkhard; Rapti, Aleka (Fundacja Rozwoju Systemu Edukacji, 2010)
The dictionary is ment to introduce the German university terminology to the Polish students completing part of their studies in Germany.
Unilex. Universitätswörterbuch Deutsch-Polnisch
Keywords: university language; academic terminology; glossary of academic terminolgy; Universitätsterminologie; Hochschulterminologie; terminologia uniwersytecka; język specjalistyczny; language for specific purposes